Effectiveness of autogenic training and affect regulation training on anxiety sensitivity in women with type-2 Diabetes - Aliyazdi, Masoume; Agahheris, Mojgan; Nouhi, Shahnaz (Researcher Bulletin of Medical Sciences, 2021)
Aims: Diabetes and intermittent periods of fluctuations in blood sugar levels are associated with stress and negative emotions. Due to the fact that these patients are prone to emotional problems, the aim of this study was to evaluate the effectiveness of autogenic training and affect regulation training on anxiety sensitivity in women with type-2 diabetes. Materials and Methods: This was a quasi-experimental study with pre-test and post-test design and control group. The statistical population included all women with type-2 diabetes in Tehran who referred to diabetes control centers in 2020. Among them, 45 people were selected by available sampling and replaced in two experimental and one control groups. All three groups completed anxiety sensitivity questionnaire. Autogenic training and affect regulation training were performed on the experimental groups. Data were analyzed using SPSS software version 24 and multivariate analysis of variance. Results: The analysis of the results showed that both autogenic training and affect regulation training reduced anxiety sensitivity in women with type 1 diabetes (p<0.00), but the effectiveness of autogenic training was not significantly different from affect regulation training (p >0.001). Conclusion: Therefore, it can be said that affect regulation training by accepting and expressing the negative emotions, reduced anxiety sensitivity in women with type-2 diabetes. Also, people with high anxiety sensitivity are incapable of moment-to-moment awareness without judgment. Thus, through autogenic training, the skill of processing thoughts and observing emotion as objective events in the mind is strengthened.